225 THE CALCIUM-PERMEABLE ION CHANNEL TRPM7 MAY PLAY A ROLE IN CELL MOTILITY AND WOUND REPAIR IN RAT CARDIAC FIBROBASTS. (1st January 2005) - Moore, J. E.; Runnels, L. W.; Greka, A.; Navarro, B.; Clapham, D. E.
Abstract : Background: The transient receptor potential channel M7 (TRPM7) is a ubiquitously expressed divalent cation selective ion channel with the exceptional feature of also being a serine/threonine kinase. TRPM7 is part of the TRP ion channel superfamily implicated in the control of calcium entry into cells. TRP channels are likely regulators of cellular responses such as neuronal bursting activity, fluid secretion, and cardiac rhythmicity. While previous work has demonstrated TRPM7 is regulated by the phosphatidylinositol 4, 5-bisphosphate (PIP2) second messenger system, its actual role in cellular signaling and calcium regulation has been unclear to date. Objective and Methods: We have studied rat cardiac fibroblasts as a naturally occurring model system for TRPM7. These studies made use of specific antibodies (polyclonal/monoclonal), confocal imaging, calcium fluorescent imaging, and electrophysiology. Results: 1) Antibodies and confocal microscopy demonstrate that in the unstimulated fibroblast, TRPM7 is actually localized intracellularly. Subsequent stimulation by growth factors (PDGF, EDGF) induces TRPM7's translocation to the plasma membrane via RAC (a member of the RHO GTPase second messenger family). 2) TRPM7 insertion into the membrane was nonuniform, seeming to be localized to areas of the cell that were spreading and moving forward (lamellipodia). 3) Both calcium fluorescent dyes and patch clamp studies demonstrated that TRPM7 activation at the plasma membrane by PDGF allows for calcium influx across the plasma membrane and a rise in intracellular calcium. 4) TRPM7 channel insertion into the membrane, channel activity, and intracellular calcium elevations are abolished by specific inhibitors such as the dominant negative form of RAC (RACN17), wortmannin and extracellular magnesium respectively. Conclusion: We have shown for the first time that activated TRPM7 localizes to focal adhesions and lamellipodia, increasing cellular free calcium, and is likely involved in cytoskeletal remodeling necessary for cell motility and wound healing in fibroblasts.